2013
DOI: 10.5194/hess-17-1809-2013
|View full text |Cite
|
Sign up to set email alerts
|

Reducing cloud obscuration of MODIS snow cover area products by combining spatio-temporal techniques with a probability of snow approach

Abstract: Abstract. Satellite remote sensing can be used to investigate spatially distributed hydrological states for use in modeling, assessment, and management. However, in the visual wavelengths, cloud cover can often obscure significant portions of the images. This study develops a rule-based, multistep method for removing clouds from MODIS snow cover area (SCA) images. The methods used include combining images from more than one satellite, time interpolation, spatial interpolation, and estimation of the probability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…In order to minimise the cloud data gaps from the validated MODIS snow products, we have applied a rigorous non-spectral cloud removal technique, partially following Wang et al (2009), Gurung et al (2011) and López-Burgos et al (2013). These studies have found the adopted cloud removal technique remarkably efficient in cloud reduction/removal from the MODIS snow products, with few season-dependent trade-offs, resulting in snow maps in good agreement with the ground snow observations.…”
Section: Cloud Removal Technique and Its Validationmentioning
confidence: 99%
“…In order to minimise the cloud data gaps from the validated MODIS snow products, we have applied a rigorous non-spectral cloud removal technique, partially following Wang et al (2009), Gurung et al (2011) and López-Burgos et al (2013). These studies have found the adopted cloud removal technique remarkably efficient in cloud reduction/removal from the MODIS snow products, with few season-dependent trade-offs, resulting in snow maps in good agreement with the ground snow observations.…”
Section: Cloud Removal Technique and Its Validationmentioning
confidence: 99%
“…However, optical images are obscured by clouds, which limit the direct usage of optical data (Gafurov & Bárdossy, ). Currently, there have been many mature cloud removal methods, including methods based on temporal and spatial continuity (Gafurov & Bárdossy, ; López‐Burgos et al, ; Paudel & Andersen, ) and methods combining multiple sensor data (Gao, Xie, Lu, et al, ; Gao, Xie, Yao, et al, ; Liang et al, ), which can reduce cloud cover and increase data availability by gap filling approaches and/or compositing.…”
Section: Introductionmentioning
confidence: 99%
“…Şensoy and Uysal (2012) presented the probability approach in snow depletion forecasting with a limited number of MODIS snow cover data. López-Burgos et al (2013) used the locally-weighted logistic regression (LWLR) method to estimate probabilistic snow occurrences for developing the cloud removal technique. Gafurov et al (2015) presented a methodology mainly based on correlations between station records and spatial snow-cover patterns, for reconstructing past snow cover using historical in situ snow-depth data, remote sensing snow-cover data and topographic data.…”
Section: Introductionmentioning
confidence: 99%